How Do Social Media Affect Analyst Stock Recommendations? Evidence from S&P 500 Electric Power Companies’ Twitter Accounts - Kim, Eun-Hee; Youm, Yoo Na (Strategic Management Journal, 2017)
[Research summary: The importance of firm-stakeholder relationships is gaining increasing attention. Although a theory of the drivers and consequences of stakeholder pressure has been developing, it focuses on pressures from organized stakeholders such as shareholders, NGOs, and activists, and does not incorporate the emerging possibility that individual voices may matter. By exploring corporate Twitter, which facilitates movement of individual stakeholders such as customers to a higher stakeholder class by providing them with a greater sense of power and urgency, we study the circumstances under which customer voices significantly affect analyst stock recommendations. We find that favorable reactions to firm-initiated messages matter, directly or indirectly, depending on the messages’ growth implications. Customer-initiated negative messages have a significant impact only with high volume and formal institutions that support customer opinions. Managerial summary:Social media is increasingly used by firms for disclosing information and engaging stakeholders. Yet, we know little about whether and how social media usage matters. We show how corporate Twitter usage may influence analyst stock recommendations. Our interviews of securities analysts suggest that social media is not institutionalized yet, but increasingly used as a source of channel checks, especially for vibes, validations, and so on. Our analyses of corporate Twitter accounts show that both firm-initiated and customer-initiated tweets can have significant impact on analyst recommendations under certain conditions. For firm-initiated tweets, the extent of retweets is an important factor, along with the content of tweets, in particular, growth implications. For customer-initiated tweets, negative tweets matter, but only with high volume and regulatory structure that supports customer protection.]